2016
DOI: 10.1002/2015gl066917
|View full text |Cite
|
Sign up to set email alerts
|

Source analysis of a potential hydraulic‐fracturing‐induced earthquake near Fox Creek, Alberta

Abstract: An earthquake with a reported magnitude of 4.4 (ML) was detected on 13 June 2015 in western central Alberta, Canada. This event was the third felt earthquake this year near Fox Creek, a shale gas exploration region. Our results from full moment tensor inversions of regional broadband data show a strong strike‐slip mechanism with near‐vertical fault plane solutions. The decomposition of the moment tensor solution is overwhelmingly double couple, while only a modest (∼20%) contribution is attributed to compensat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
2

Year Published

2016
2016
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 71 publications
4
56
2
Order By: Relevance
“…For two clusters (SS10 and SS17), dense‐array double‐difference relocations corroborate the sense of slip as N‐S dextral motion (Figures and ), similar to the findings of Bao and Eaton [] for SS6. In the NE cluster of SS10, we observe subvertical faults with strike orientations of 357° ± 4°, which is within the error range of other reported focal mechanism determinations (354° ± 1°) [ Wang et al ., ]. Similarly, orientations determined for the subvertical fault in SS17 suggest an azimuth of 187° ± 35° in comparison to the focal mechanism strike of 184° ± 3°.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…For two clusters (SS10 and SS17), dense‐array double‐difference relocations corroborate the sense of slip as N‐S dextral motion (Figures and ), similar to the findings of Bao and Eaton [] for SS6. In the NE cluster of SS10, we observe subvertical faults with strike orientations of 357° ± 4°, which is within the error range of other reported focal mechanism determinations (354° ± 1°) [ Wang et al ., ]. Similarly, orientations determined for the subvertical fault in SS17 suggest an azimuth of 187° ± 35° in comparison to the focal mechanism strike of 184° ± 3°.…”
Section: Discussionmentioning
confidence: 91%
“…The first occurred on 13 June 2015, as part of SS10. It was initially reported as having a magnitude of 4.4 M L , with the moment magnitude later reported as M 3.9 [ Wang et al ., ]. The second occurred on 12 January 2016 as part of SS17; the initial magnitude of 4.8 M L was later revised to a value of M 4.1.…”
Section: Spatial Distribution Of Induced Seismicity Near Fox Creekmentioning
confidence: 84%
See 2 more Smart Citations
“…In hydraulic fracturing, the volume and duration of fluid injection are lower, but the pressure is much higher, compared to wastewater disposal; therefore, they have different potential risks for inducing earthquakes (Walters et al, ). Hydraulic fracturing is expected to generate microearthquakes with magnitude −3 < M < 0, since the intent is to create fractures restricted to the target formation (Maxwell, ; Rubinstein & Mahani, ; Warpinski et al, ); however, several studies have reported the occurrence of M > 1 earthquakes induced by hydraulic fracturing in Oklahoma (Holland, ), Ohio (Friberg et al, ; Skoumal et al, , ), United Kingdom (Clarke et al, ), and western Canada, in northeast British Columbia and northwest Alberta (Atkinson et al, ; Bao & Eaton, ; British Columbia Oil and Gas Commission (BCOGC), , ; Farahbod et al, ; Schultz, Mei, et al, ; Schultz, Stern, et al, ; Schultz et al, ; Wang et al, ), including a M 4.6 event in British Columbia (Atkinson et al, ). These events are likely caused by reactivation of nearby critically stressed faults that are well oriented to slip in the local stress field (Maxwell, ).…”
Section: Introductionmentioning
confidence: 99%